Xenopus Models of Cancer: Expanding the Oncologist’s Toolbox - Hardwick, Laura J. A.; Philpott, Anna (Frontiers in Physiology, 2018)
The use of the Xenopus model system has provided diverse contributions to cancer research, not least because of the striking parallels between tumour pathogenesis and early embryo development. Cell cycle regulation, signalling pathways and cell behaviours such as migration are frequently perturbed in cancers; all have been investigated using Xenopus, and these developmental events can additionally act as an assay for drug development studies. In this mini-review, we focus our discussion primarily on whole embryo Xenopus models informing cancer biology; the contributions to date and future potential. Insights into tumour immunity, oncogene function and visualisation of vascular responses during tumour formation have all been achieved with naturally occurring tumours and induced-tumour-like-structures (ITLS) in Xenopus. Finally, as we are now entering the era of genetically modified Xenopus models, we can harness genome editing techniques to recapitulate human disease through creating embryos with analogous genetic abnormalities. With the speed, versatility and accessibility that epitomise the Xenopus system, this new range of pre-clinical Xenopus models has great potential to advance our mechanistic understanding of oncogenesis and provide an early in vivo model for chemotherapeutic development.